Linking admin data to explore labour market and health outcomes for refugees - the RIO study. - Evans, Alan; Frowen, Sam (International Journal of Population Data Science, 2025)
Evidence on refugee integration outcomes in the UK is lacking, partly due to an absence of datasets which permit refugees to be identified. The RIO longitudinal cohort study designed in collaboration with the Home Office and MHCLG aims to address this by linking various administrative data longitudinally. RIO covers cohorts granted asylum and those who resettled in the UK via several resettlement schemes between 2015 and 2023. Administrative datasets linked to the RIO cohorts include the Personal Demographic Service (PDS), Home Office Borders and Immigration (HOBI) data, Births, Deaths and 2021 Census. Our latest iteration linked Pay as you earn (PAYE), Energy performance certificate (EPC) and Valuation Office Agency (VOA). Alongside improvements to our deterministic and associative linkage algorithms, we’ve now incorporated Ministry of Justice’s Splink coding package to enable us to link via probabilistic methods and further improve our linkage rates and quality. Experimental analysis has looked at social and economic outcomes for these refugee cohorts. Linkage to NHS data helps us understand access to health services and time taken to access these services once resettled. Our publication due for release in April 2025 provides us with a rich understanding and evidence of how linked administrative and Census data can bridge the gap in understanding of how refugees integrate into the labour market and housing systems in the UK up to 6 years after their arrival or grant of asylum. We also break these insights down into key characteristics to not only show how integration varies by asylum and refugee cohorts but also by age, sex and geographical region. RIO will ultimately help inform local authorities, government, charities and other organisations with resource allocation for these vulnerable populations. We are planning to make this dataset available to Accredited Researchers via the ONS Secure Research Service (SRS) and the Integrated Data Service (IDS).